Diagnostic value of [68Ga]Ga-FAPI-04 in patients with colorectal cancer in comparison with [18F]F-FDG PET/CT - Lin, Xinfeng; Li, Yingjie; Wang, Shuailiang; Zhang, Yan; Chen, Xuetao; Wei, Maomao; Zhu, Hua; Wu, Aiwen; Yang, Zhi; Wang, Xuejuan (Frontiers in Oncology, 2023)
Purpose: This study aimed to compare the diagnostic performance of [68Ga]Ga-FAPI-04 PET/CT and [18F]F-FDG PET/CT in primary and metastatic colorectal cancer (CRC) lesions. Methods: This single-center preliminary clinical study (NCT04750772) was conducted at the Peking University Cancer Hospital & Institute and included 61 participants with CRC who underwent sequential evaluation through PET/CT with [18F]F-FDG and [68Ga]Ga-FAPI-04. Their PET/CT images were analysed to quantify the uptake of the two tracers in the form of maximum standardised uptake (SUVmax) values and target-to-background ratio (TBR), which were then compared using Wilcoxon’s signed-rank test. The final changes in the tumour–node–metastasis (TNM) stage of all participants were recorded. Results: Of all the participants, 21 were treatment naïve and 40 had been previously treated. In primary CRC lesions, the average TBRs of [68Ga]Ga-FAPI-04 and [18F]F-FDG were 13.3 ± 8.9 and 8.2 ± 6.5, respectively. The SUVmax of [68Ga]Ga-FAPI-04 in signet-ring/mucinous carcinomas (11.4 ± 4.9) was higher than that of [18F]F-FDG (7.9 ± 3.6) (P = 0.03). Both median SUVmax in peritoneal metastases and TBR in liver metastases of [68Ga]Ga-FAPI-04 were higher than those of [18F]F-FDG (5.2 vs. 3.8, P < 0.001; 3.7 vs. 1.9, P < 0.001, respectively). Compared with [18F]F-FDG PET/CT, clinical TNM staging based on [68Ga]Ga-FAPI-04 PET/CT led to upstaging and downstaging in 10 (16.4%) and 5 participants (8.2%), respectively. Therefore, the treatment options were changed in 13 participants (21.3%), including 9 with additional chemo/radiotherapy and/or surgery and others with avoidance or narrowed scope of surgery. Conclusion: [68Ga]Ga-FAPI-04 showed potential as a novel PET/CT tracer to detect lymph nodes and distant metastases, which improved CRC staging, thus prompting the optimisation or adjustment of treatment decisions.